Caspases help to spread the message via extracellular vesicles - Hill, C; Dellar, E; Baena Lopez, LA (Wiley, 2022)
Cell-cell communication is an essential aspect of multicellular life, key for coordinating cell proliferation, growth, and death in response to environmental changes. Whilst caspases are well-known for facilitating apoptotic and pyroptotic cell death, several recent investigations are uncovering new roles for these enzymes in biological scenarios requiring long-range intercellular signalling mediated by extracellular vesicles (EVs). EVs are small membrane-bound nanoparticles released from cells that may carry and deliver cargo between distant cells, thus helping to coordinate their behaviour. Intriguingly, there is emerging evidence indicating a key contribution of caspases in the biogenesis of EVs, the selection of their cargo content, and EV uptake/function in recipient cells. Here, we discuss the latest findings supporting the interplay between caspases and EVs, and the biological relevance of this molecular convergence for cellular signalling, principally in non-apoptotic scenarios.